Transformational Islamic Religious Education: The Role of Self-Efficacy in the Formation of Students' Religious Character - Lu'Lu' Husniah; Edi Suresman; Mokh. Iman Firmansyah; Farhatul Muthi’ah (Mimbar Agama Budaya, 2025)
Islamic religious education in the modern era must be informative and transformational, namely, to be able to form students' religious character completely and sustainably. One of the key factors in the success of this transformation is self-efficacy, namely, students' belief in their ability to carry out religious values in everyday life. This study aims to examine how the role of self-efficacy is built through Islamic Religious Education learning that is designed contextually and applicatively. This study uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The study subjects consisted of Islamic Religious Education teachers and senior high school students implementing transformation-based learning in Bandung. The study results show that students' self-efficacy is formed through 1) a religious and supportive school environment, 2) a meaningful and contextual learning model, 3) consistent character guidance and habituation, and 4) disciplinary policies that support student self-control. Therefore, transformational Islamic Religious Education is effective in forming students' religious character if it synergistically involves all elements of the school to strengthen their self-efficacy in carrying out religious teachings consistently and consciously.